DESIGN AND DEVELOPMENT OF LIFE STORY AND WISDOM OF THE ELDERY SHORT FILM - Deli Deli; Jose Armando (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The increasing population of elderly people has become a globalphenomenon. Most developing countries have had this special achievement, including southeast Asia, countries like Singapore, Indonesia. Storytelling is the activity of telling stories. Digital video is rapidly spreading across modern life from telivision to Youtube to private streaming channels. Technological advances in Digital Video have been widely use and availability in the field of social services, Digital Video provides new possibilities for service provision, allows elderly people to provide stories of their life experiences, and new possibilities for social research, through recording and analyzing data video